KONTRIBUSI KOORDINASI MATA TANGAN DENGAN KETEPATAN HASIL SERVICE ATAS BOLA VOLI PADA TIM PUTRI ANJUNGAN JUNIOR PEKANBARU - Putra, Sardi Saka; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem of this research was based on the observation in the field when the female team of Anjungan Junior Pekanbaru did exercise and match. The team still lost in the match. It happened because the team failed in doing upper service. This research aimed to figure out that there was the contribution of wrist and service accuracy coordination in volley ball for female team of Anjungan Junior Pekanbaru. The sampling technique was total sampling for female team of Anjungan Junior Pekanbaru. The sample of this research was the female team of Anjungan Junior Pekanbaru which was the amount of 12 people. Based on the analysis of X and Y contribution, rtable was in a significant level Î± ( 0.05 ) = 0.576. It meant rcount ( 1,21 ) >rtable ( 0.576 ) which there was relationship. Then, there was a contribution test by using the formula KD = r2 x 100%. The result showed that there was contribution of wrist and service accuracy coordination in volley ball for female team of Anjungan Junior Pekanbaru with the contribution of 1.21 % and other factors of 98.79%.Keywords : the contribution of wrist and service accuracy coordination